Hak dan Kewajiban Warga Negara dalam Islam dan UUD 1945 : Studi Komparatif - Muhammad Yusuf; Syamzaimar (Sinergi : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to comparatively examine the rights and obligations of citizens as regulated in Islamic teachings and the 1945 Constitution of the Republic of Indonesia. Using a qualitative approach with normative juridical and literature study methods, this research analyzes primary sources including the Quran, Hadith, fiqh literature, and the 1945 Constitution along with its amendments. The concept of human rights in Islam is rooted in the principle of human dignity (karamah insaniyah) and the role of humans as khalifatullah fil ardh, while the 1945 Constitution grounds rights in the Pancasila philosophy as a national social agreement. The results show that there are significant similarities between Islamic concepts and the 1945 Constitution regarding fundamental rights—such as the right to life, education, justice, and freedom of religion—as well as citizen obligations in upholding law, participating in state defense, and contributing to social welfare. However, differences also emerge in the philosophical foundation: Islam grounds rights and obligations in divine revelation (wahyu) and the concept of khalifah, while the 1945 Constitution is based on the Pancasila philosophy as a social agreement. This study further demonstrates that these differences are not contradictory but complementary, as evidenced by various national legislations that accommodate Islamic values, such as the Marriage Law, Zakat Law, and Islamic Law Compilation. This study concludes that Islamic values and the 1945 Constitution are not contradictory but complementary in building a just, prosperous, and civilized Indonesian society. Keywords: citizen rights, citizen obligations, Islam, 1945 Constitution, comparative study Abstrak Penelitian ini bertujuan untuk mengkaji secara komparatif hak dan kewajiban warga negara sebagaimana diatur dalam ajaran Islam dan Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 (UUD 1945). Dengan menggunakan pendekatan kualitatif dengan metode yuridis normatif dan studi kepustakaan, penelitian ini menganalisis sumber-sumber primer meliputi Al-Quran, Hadits, literatur fikih, serta UUD 1945 beserta amandemennya. Konsep hak asasi manusia dalam Islam berakar pada prinsip kemuliaan manusia (karamah insaniyah) dan peran manusia sebagai khalifatullah fil ardh, sementara UUD 1945 mendasarkan hak-hak tersebut pada filosofi Pancasila sebagai kesepakatan sosial bangsa. Hasil penelitian menunjukkan terdapat kesamaan yang signifikan antara konsep Islam dan UUD 1945 dalam hal hak-hak dasar—seperti hak hidup, pendidikan, keadilan, dan kebebasan beragama—maupun kewajiban warga negara dalam menegakkan hukum, berpartisipasi dalam bela negara, dan berkontribusi terhadap kesejahteraan sosial. Penelitian ini lebih lanjut menunjukkan bahwa perbedaan-perbedaan tersebut tidaklah bersifat kontradiktif melainkan saling melengkapi, sebagaimana terbukti dalam berbagai legislasi nasional yang mengakomodasi nilai-nilai Islam. Penelitian ini menyimpulkan bahwa nilai-nilai Islam dan UUD 1945 tidaklah bertentangan melainkan saling melengkapi dalam membangun masyarakat Indonesia yang adil, makmur, dan beradab. Kata Kunci: hak warga negara, kewajiban warga negara, Islam, UUD 1945, studi komparatif